Endoparasites in Grey Seals (Halichoerus grypus) By-Caught in Latvian Commercial Coastal Fishery - Maija Selezņova; Aivars Cīrulis; Maira Mateusa; Ēriks Krūze; Loreta Rozenfelde; Inga Pigiņka-Vjačeslalova; Lilija Geine-Romanova; Didzis Ustups; Gunita Deksne (Animals)
The grey seal (Halichoerus grypus) is a fish-eating mammal and an apex predator in the Baltic Sea. It serves as the definitive host for several parasite species that utilize fish as intermediate or paratenic hosts. This study aimed to determine the endoparasite fauna of grey seals by-caught in the Latvian commercial coastal fishery and to analyze the impact of parasites on the seals’ nutritional status. A total of 59 grey seals were collected for parasitological analysis. Six parasite species were identified, with all seals infected by Contracaecum sp. and Corynosoma semerme. High prevalence rates were observed for Corynosoma strumosum (69.4%), Parafilaroides gymnurus (44.8%), and Pseudamphistomum truncatum (27.1%). Giardia duodenalis was detected in two animals, marking its first report in the Baltic Sea grey seals. A significant negative correlation was found between the infection intensity of C. semerme (Rs = −0.324, p = 0.013) and the nutritional status of the grey seals.